2019
DOI: 10.1016/j.apsusc.2019.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Defect engineered MoSSe Janus monolayer as a promising two dimensional material for NO2 and NO gas sensing

Abstract: Gas sensing mechanism of H 2 S, NH 3 , NO 2 and NO toxic gases on transition metal dichalcogenides based Janus MoSSe monolayers are investigated using the density functional theory. The pristine and defect included MoSSe layers are considered as a host material for adsorption study. Three types of defects (i) molybdenum vacancy, (ii) selenium vacancy, and (iii) sulfur/selenium vacancy are studied to understand their impact on electronic properties and sensing of these gas molecules. The formation energy is com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 57 publications
1
44
0
Order By: Relevance
“…10 On the other hand, the intrinsic dipole of MoSSe (structural symmetry of MoS 2 is broken) modifies the electronic properties. 11 A number of theoretical studies have shown that two-dimensional Janus materials perform well in gas sensors, 12,13 photocatalytic water splitting, [14][15][16] field-effect transistors, 17 and solar cells. 18,19 However, practical use of MoSSe in a device will require a contact with metal electrodes to enable injection of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…10 On the other hand, the intrinsic dipole of MoSSe (structural symmetry of MoS 2 is broken) modifies the electronic properties. 11 A number of theoretical studies have shown that two-dimensional Janus materials perform well in gas sensors, 12,13 photocatalytic water splitting, [14][15][16] field-effect transistors, 17 and solar cells. 18,19 However, practical use of MoSSe in a device will require a contact with metal electrodes to enable injection of carriers.…”
Section: Introductionmentioning
confidence: 99%
“…43 Chaurasiya et al have found that intrinsic defects can effectively alter the adsorption behaviors of NO 2 , NO, and NH 3 on Janus MoSSe sheet. 44 However, the detailed role of the intrinsic defects on introducing the adsorption state and enhancing the photoreaction of water is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…From this point of view, Janus monolayer has excellent potential candidates to realize superior sensitivity without gate bias. Some of the work has been reported on various gas molecules detection for gas sensing devices [ 35 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. Still, there is a need for a better understanding of various gas sensing properties of the Janus monolayer.…”
Section: Introductionmentioning
confidence: 99%